Religious trauma and moral injury from LGBTQA+ conversion practices. (July 2022) - Jones, Timothy W.; Power, Jennifer; Jones, Tiffany M.
Abstract: Religion-based LGBTQA + conversion practices frame all people as potential heterosexuals whose gender aligns with their birth sex (in a cisgender binary model of male and female sexes). Deviation from this heterosexual cisgender social identity model is cast as curable 'sexual brokenness'. However, research shows conversion practices are harmful, and particularly associated with increased experiences of abuse, mental health diagnoses, and suicidality. This paper explores their contribution to the particular harms of moral injury and religious trauma, drawing firstly on the foundational moral injury literature to offer a unique conceptual framework of spiritual harm and moral injury, and secondly on a rare qualitative 2016–2021 study of the spiritual harms reported in semi-structured interviews of 42 survivors of LGBTQA + change and suppression practices in Australia. The paper examines the survivors' support needs around the nature and extent of religious trauma and moral injury, to inform services working towards supporting their recovery from such experiences and their resolution of conflicts deeply bound in their sense of self and belonging. It argues that impairment of conversion survivors' relationships with religious communities, and religious self-concepts, point to the need for additional improvements in pastoral practice. Highlights: Research shows a globally common range of religion-based LGBTQA + conversion practices. Spiritual harms associated with conversion practices have not yet been investigated. Coercion in conversion practices was linked to stronger religious trauma responses. Complicity in experiences of conversion practices was closely linked to moral injury. Attending to spiritual and cultural factors will aid in survivors' recovery.